Tobacco smoking and COVID-19 infections: A summary of facts from scientific literature - Aryal, Umesh Raj (Journal of Kathmandu Medical College, 2020)
The objective of the study is to summarise the association between COVID-19 and smoking published in peer-reviewed journals, preprint in MedRxiv /Qeios, news, and report. The literature search was conducted between 1st to 20th August 2020 using three databases (PubMed, Google Scholar, and Google) with the keywords “Tobacco smoking and COVID-19” as search terms. A French study claimed that smoking is a protective agent for COVID-19 infections. A meta-analysis revealed that tobacco smoking is significantly associated with COVID-19 infections. Despite the controversy surrounding the connection between smoking and COVID-19, people should not smoke or use any tobacco products because smoking is associated with increased rates of severe COVID-19.